255 Evaluation of Different Corn Milling Methods for High-moisture and Dry Corn on Nutrient Digestion. (7th May 2021) - Coulson, Caitlin A; Woita, Nicole; Spore, Tyler; Wilson, Hannah; Butterfield, Kylie; Erickson, Galen E
Abstract: A 2 × 2 factorial digestion study using seven ruminally cannulated steers evaluated the effect of feeding diets containing 70% (dry matter-basis) high-moisture (HMC) or dry corn (DC), processed with either a hammer mill or Automatic Ag Roller Mill (Pender, NE), on nutrient digestion. Feeding HMC decreased the amount of excreted dry matter (DM) and organic matter (OM; P ≤ 0.01) regardless of mill type, but there was a tendency (P ≤ 0.13) for an interaction between corn type and mill type for DM and OM digestibility. There was no difference between either milling treatments fed as HMC (P ≥ 0.69), but the hammer mill DC diet was more digestible than the roller mill DC (P = 0.05). There was no effect on NDF digestibility, but there was a tendency for an interaction between grain type and processing method for ADF digestibility, with the roller mill DC diet having the lowest (P = 0.02) ADF digestibility and no differences (P ≥ 0.15) among the other treatments. As expected, HMC based diets had greater (P < 0.01) starch digestibility compared to DC, but milling method had no effect (P = 0.56). High moisture corn diets had greater (P = 0.01) DE intake (Mcal/kg), and hammer mill DC tended to be greater (P = 0.07) than roller mill DC. There tended (P = 0.07) to be an interaction for minimum pH, with roller mill HMC and hammer mill DC having the lowest average pH, but not different from hammer mill HMC (P ≥ 0.32). There were no differences (P = 0.56) in average pH, but HMC diets had greater variance (P = 0.04) and greater area under pH 5.6 (P = 0.05) compared to DC based diets. Feeding cattle HMC compared to DC increases nutrient digestibility but milling process had little impact.